The effect of different concentrations of metformin drug on the concentration of glucose and lipid profile in the male rats induced diabetes by alloxan. - Inas Mujil Nayef Al-janabi; Wahby Abdulqader Salman Alhamdany (Tikrit Journal of Pure Science, 2022)
The present study aimed to find out the effect of Metformin drug on some of biochemical parameters, including Glucose and lipid profile: Cholesterol, Triglycerides, High density lipoprotein HDL-CH, and low density lipoprotein LDL-C Male albino rats were used in this study.